Carbon Sequestration And Economic Potentials Of Developing Shrub Willow Biomass In Kastamonu Region, Turkey - Aydin, Mirac; Sivacioglu, Ahmet; Pacaldo, Renato S. (Aperta, 2017)
Shrub willow biomass (SWB) is not among the fast-growing species being developed into a largescale plantation in Turkey. Thus, the economic and carbon sequestration potentials of this species are not well explored. This study assesses the economic and carbon sequestration potentials of developing shrub willow biomass (SWB) in the Kastamonu Forest Directorate (KFD) region, Turkey. We used GIS to determine the size of potential planting area. We evaluated the economic returns of three biomass yield scenarios: 22.5- Mg ha(-1) yr(-1) as a best-case (BC) scenario, 15.0- Mg ha(-1) yr(-1) as an average-case (AC) scenario, and 10.0 -Mg ha(-1) yr(-1) as a worst-case (WC) scenario. We also determine the carbon sequestration potential of SWB production based on biomass productions in the aboveground stool, belowground stool, and coarse roots. GIS analysis revealed that about 1,388.85-km(2) of lands could be utilized for planting SWB. At $50 -Mg-1 (wet wt.) purchase price, farmers could potentially earn income ranging from $2,033- to $3,099 -ha(-1) every 3 years, depending on biomass yields. The estimated internal rate of return (IRR) ranged from 8.1% for the WC scenario to 25.4% for the BC scenario. A grower's investments is likely to be paid back at about age 7 for the BC scenario, and at age 10 for the AC scenario. The net amount of C sequestration is about 34.5 -Mg CO(2)e ha(-1) at the end of 22 years. Our results suggest that SWB productions in the KFD region are doable due to availability of large potential planting areas, viable economic returns, and C sequestration potentials.
Keywords: 2. Zero hunger; 15. Life on land; 7. Clean energy